Adsorption of Water Molecules on Pristine and Defective NiPX3 (X: S, Se) Monolayers. Issue 11 (3rd October 2021) - Wu, Zhicheng; Xu, Sifan; Zhou, Yong; Guo, Qilin; Dedkov, Yuriy; Voloshina, Elena
Abstract: Layered transition metal trichalcogenides MPX3 (M: transition metal; X: S, Se) demonstrate a wide spectrum of properties and are widely proposed as effective materials for the water splitting reactions. Among these materials, NiPX3 are the most promising ones because their electronic structures, band gaps and positions of the valence and conduction bands edges fit to the potentials characteristic for the oxygen and hydrogen evolution reactions. Here, first steps of a detailed theoretical description on the adsorption of water molecules on pristine and defected (chalcogen vacancies) surfaces of NiPX3 are presented and it is shown that in all cases a physisorption takes the place with adsorption energies do not exceeding −650 meV and water dissociative adsorption is unfavorable. This work provides a general description for water molecules interaction with MPX3 and can serve as a basis for further studies on more complicated water/MPX3  reactions. Abstract : NiPX3 (X: S, Se) are representative examples of a new class of 2D layered materials—transition metal trichalcogenides. For the first time, a theoretical analysis of the interaction of water molecules with NiPX3 monolayers has been performed. The influence of chalcogen atoms as well as defects on water adsorption and dissociation is considered.